2000
DOI: 10.1046/j.1365-3148.2000.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential leucocyte subpopulation analysis of leucodepleted red cell products

Abstract: Donor leucocytes are responsible for many adverse transfusion effects. Clinical reactions may be attributed to specific leucocyte subsets. In this study leucocyte subpopulations were identified and quantified pre- and post-leucodepletion by integral filtration using novel Optipac(R) configurations incorporating either WBF-1 (Pall Medsep) or RS2000 (Asahi) whole blood filters. Leucocytes were analysed by flow cytometry using direct, four-colour, membrane immunofluorescence with monoclonal antibodies specific fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…We hypothesize that these extraregional events are fragments of polymorphonuclear neutrophil (PMN) nuclei (lobes), based on the fact that they do not occur in the absence of WBC and that they stain with PI (which is specific for nucleic acid) but at a lower fluorescence intensity than WBC. This is further supported by the fact that these extraregional events occur mainly in leucocyte‐depleted red cell products which contain predominantly granulocytes [6] and rarely occur in leucocyte‐depleted platelets that contain predominantly mononuclear cells [7]. Although it is well known that WBC in blood components undergo apoptosis during storage [8,9], this has not been shown to be the cause of these events in the low‐level WBC counting setting.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that these extraregional events are fragments of polymorphonuclear neutrophil (PMN) nuclei (lobes), based on the fact that they do not occur in the absence of WBC and that they stain with PI (which is specific for nucleic acid) but at a lower fluorescence intensity than WBC. This is further supported by the fact that these extraregional events occur mainly in leucocyte‐depleted red cell products which contain predominantly granulocytes [6] and rarely occur in leucocyte‐depleted platelets that contain predominantly mononuclear cells [7]. Although it is well known that WBC in blood components undergo apoptosis during storage [8,9], this has not been shown to be the cause of these events in the low‐level WBC counting setting.…”
Section: Introductionmentioning
confidence: 99%
“…The flow characteristics are also confounded by the fact that older units also contain fewer intact WBCs, and WBC fragments may not be removable by filtration. In addition, characteristics of the filter itself, such as the electrical charge of the filter material, may result in varying efficiencies of filtration as well as different WBC subtype populations in the final component 32–34 . In our study, the age of the units was restricted, which limited the impact of this variable.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…It is well known that, as the donor WBC count increases, the number of WBCs that will remain in the final component increases as well 22 . Hemoglobinopathies such as sickle cell trait can also affect the effectiveness of filtration 34–36 . It is quite possible that other hematologic abnormalities (including other RBC membrane, WBC, and plasma abnormalities) or unknown donor factors may also affect filtration rates and effectiveness.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Rider et al 22 compared WBC subset depletion after filtration after brief storage at room temperature in 20 units from 26 healthy volunteer donors. This study found that WBC levels in all units after filtration by either WBF‐1 or RS2000 filters were within acceptable WBC‐reduction ranges, with granulocytes and monocytes equally dominant followed by lymphocytes.…”
Section: Discussionmentioning
confidence: 99%